Pengaruh Net Profit Margin (NPM), Debt to Equity Ratio (DER), dan Price to Book Value (PBV) Terhadap Harga Saham Perusahaan Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Nugraha, Nizar Alfa; Khalikussabir, Khalikussabir; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research was conducted to see the effect of Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Price to Book Value (PBV) on the Stock Price of Coal Mining Companies in Indonesia. Value (PBV) on the Share Price of Coal Mining Companies Listed on the Indonesia Stock Exchange 2018-2022. Listed on the Indonesia Stock Exchange 2018-2022. Population in research This study is a coal production mining company with a total sample of 12 companies, using non-probability sampling techniques. companies, using non-probability sampling techniques and purposive sampling methods. and purposive sampling method. Multiple linear regression and hypothesis testing used for analysis methods using SPSS (Statistical Package For Social Science) software. The results of the analysis obtained are the variables Net Profit Margin (NPM), Debt to Equity Ratio (DER), Debt to Equity Ratio (DER), and Price to Book Value (PBV) have a significant influence on Stock Price. Keywords: Net Profit Margin, Debt To Equity Ratio, Debt To Equity Ratio, Share Price